Type of army service and decision to engage in risky behavior among young people in Israel - Sharon Garyn-Tal; Shosh Shahrabani (Judgment and Decision Making, 2015)
Previous studies have examined the impact of military service on the decision to engage in risky behavior. Yet most of these studies focused on voluntary recruits, did not distinguish between legal and illegal risky activities and did not compare combat and non-combat soldiers during and after service according to gender. The current study is unique because of the nature of Israeli compulsory army service. It examines the relationship between type of army service and five legal and illegal risky behaviors for three groups: non-combat, combat without fighting experience, and combat with fighting experience. We also examine differences in the propensity for risky behavior between men, most of whom are assigned to combat units due to the army’s needs, and women, who serve in combat units on a voluntary basis only. A questionnaire survey was randomly distributed at train stations and central bus stations in Israel among 413 soldiers and ex-soldiers between the ages of 18-30. The predictor variables include type of service or battle experience, the Evaluation of Risks scale and socio-demographic characteristics. In general, we found that high percentages of young people engage in risky behavior, especially illegal behavior. The results indicate that fighting experience is significantly and positively correlated with the consumption of illegal substances for currently serving men soldiers (but not for women) and this effect is mitigated after discharge from the army. Importantly, the use of illegal substances is not a result of the individual’s preferences for engaging in various risky behaviors. Thus, our results suggest that the effect of the increased propensity toward risky behavior following the experience of fighting overrides the combat unit’s discipline for men when it comes to the consumption of illegal substances. In addition, our findings indicate that serving in a combat unit as opposed to a non-combat unit affects the tendency of women ex-combat soldiers to travel to risky destinations, though this is probably related to their original higher risk attitude, since women must volunteer for combat units.